Serotyping Isolated Strains of Salmonella for Consomption in the Eastern Logone Province in Chad - Maoudombaye, T.; Bodering, A.; Malloum, Mahamat Seid Ali; Ndoutamia, G.; Ngakou, A. (International Journal of Applied Sciences and Biotechnology, 2019)
The present work was carried out in the Doba petroleum basin, Eastern Logone Province, and focused on the serotyping of strains of salmonella isolated in well water, boreholes and rivers for the consumption of the population. The sampling was carried out according to a complete randomized device with 10 samples per source of water, making a total of 30 samples. Salmonellae were detected according to the French standard ISO 6579: 2002, followed by serotyping. The results of the biochemical identification test of the API 20 E gallery led, thanks to the Apiweb Tm-API 20E V4.1 site to Salmonella spp. The serotyping results revealed, according to the White-Kauffmann-Le Minor table, serovars Anatum, Mbandaka and Idikan. S. Anatum was detected in P4 well waters and F6 wells; S. Mbandaka, in F9 and R8 river water; and finally, S. Idikan, in F5 and R4 river water. These results show a homogeneous distribution of these serotypes in the different water sources of the study area. The presence of these pathogenic serotypes in drinking water sources attests that these waters are unhealthy in accordance with WHO's guidelines for drinking quality. Corrective measures are needed to improve the quality of these water rich in germs that may cause food poisoning.